Peran Mahasiswa Program Studi Ekonomi Islam Fakultas Ekonomi Dan Bisnis Universitas Jambi Dalam Meningkatkan Literasi Keluarga Dan Masyarakat Sekitar Tentang Perbankan Syariah - Arni Diana; Amri Amir; Rafiqi . (JOURNAL OF SHARIA ECONOMICS, 2024)
The positive movement of sharia banking in the last 2 years has not been accompanied by public literacy about sharia banking, which is only 11% with penetration below 7%. Public literacy regarding sharia banking is very minimal, where a group of individuals only "know" about the existence of sharia banking and know little about the products available in sharia banking. The reason for conducting this research is to determine the role of Islamic Economics Study Program students who have studied and are familiar with sharia banking products and contracts in increasing the literacy of families and surrounding communities about sharia banking, and the surrounding community, and to explain the role of Islamic Economics Study Program students in inviting families and surrounding communities to interact with sharia banking. The type of research the author conducted included field research. The primary data sources in this research are students of the 2018, 2019, 2020 and 2021 Islamic Economics Study Program, while the secondary data sources in this research are indirect sources such as books, journals and theses. The author's data collection techniques were carried out through interviews and documentation with data processing carried out in a qualitative descriptive manner. Based on research data, it can be concluded that students have maximally introduced sharia banking products and contracts and have invited their families and surrounding communities to interact with sharia banking. However, from the results of providing outreach there are still those who are not yet interested in interacting with sharia banks